2017
DOI: 10.1021/jacs.6b10550
|View full text |Cite
|
Sign up to set email alerts
|

Helical Self-Assembly-Induced Singlet–Triplet Emissive Switching in a Mechanically Sensitive System

Abstract: In nanoscience, chirality has shown a significant ability to tune materials' electronic properties, whereas imposing macrochirality into the regulation of singlet-triplet features of organic optoelectronics remains a challenging research topic. Since the tuning for singlet and triplet excited-state properties in a single π-functional molecule connects to its multicolor luminescent application and potential improvement of internal quantum efficiency, we here report that supramolecular chirality can be employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
105
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 166 publications
(109 citation statements)
references
References 69 publications
3
105
0
1
Order By: Relevance
“…d) CD spectra of 1 in DMF/H 2 O. Reproduced with permission from Ref. . Copyright 2017, American Chemical Society.…”
Section: Dynamic Modulation By External Stimulimentioning
confidence: 99%
“…d) CD spectra of 1 in DMF/H 2 O. Reproduced with permission from Ref. . Copyright 2017, American Chemical Society.…”
Section: Dynamic Modulation By External Stimulimentioning
confidence: 99%
“…[6] It was also demonstrated that the luminescence intensity of synthetic helicates, [7,8] aromatic foldamers, [9] peptides [10] and peptoids [11] containingc hromophores incorporated in their backbone, could be controlled by changing the chemical environment of the chromophore using solvophobic interactions, [9] pH, [11b] or binding of substrate molecules. [12] However,t he direct relationship between the conformationalo rder of peptidomimetics and ap hysical utility such as the luminescenceo fa ne mbedded metal complex, that does not involve changing its chemical environment, has not yet been reported. Linking together two fundamentalp roperties such as high-order structure and luminescence may provide fundamentali nsights on the relationship betweens tructure and function, and open new avenues for possible applications in photocatalysis, chemical biology,m olecular imaging and more.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-sulfurated aromatic compounds are prone to take effect metal-free room-temperature phosphorescence emitters in which the ISC process is environmentally adjustable. [35][36][37][38] Thec ompounds can be readily synthesized from low-cost precursors with different functional groups modified for postprocessing. [39][40][41] Herein, we designed and synthesized two fluoro-substituted tetrakis(arylthio)benzene molecules (compound 1 and 2,F igure 1), based on the anticipation that the multiple C À Sb ond can be deformable for tuning the molecular conformation with diverse intermolecular noncovalent interaction (e.g., CHÀFb ond, CH-p,S ÀSi nteraction, p-p stacking, etc.).…”
mentioning
confidence: 99%